PENGARUH DIMENSI FRAUD TRIANGLE TERHADAP KECURANGAN AKADEMIK - Muhammad Anugrah; M. Ridwan Tikollah; Fajriani Azis (Jurnal Binagogik, 2024)
This research aims to analyze the effect of the triangular dimension of fraud on academic fraud instudents of the Accounting Education Study Program class of 2019, Faculty of Economics, MakassarState University. The population of this study were all students of the Accounting Education StudyProgram, Faculty of Economics, Makassar State University in 2019. From the results of simple linearregression analysis, it was obtained that the triangular dimension of fraud Y = 8.343 + 0.453X, meaningthat for every addition of 1 value of the triangular dimension of fraud, the value of academic fraudincreased by 0.453. While the results of the analysis of the coefficient of determination is 0.298 or 29.8%,which means that the dimensions of the fraud triangle have contributed to academic fraud in 2019 FEUNM Accounting Education Study Program students of 29.8% and the remaining 70.2% is influencedby other factors. While the results of the t-test analysis obtained a significant value of 0.009 <0.05,which means that the triangular dimension of fraud has a significant effect on academic fraud, thus thehypothesis is accepted.